MENAKAR PARADIGMA DISTINGTIF MAQASHID SYARIAH DAN MAQASHID AL-QUR’AN DALAM KAJIAN ISLAM - Eman Sulaeman (LP2M Universitas PTIQ Jakarta, 2024)
This study analyzes the differences and similarities between Maqashid Syariah and Maqashid Al-Qur'an from the perspective of Islamic research. Maqashid Al-Qur'an encompasses universal moral, social, and spiritual values to guide humanity towards justice, mercy, and balance in life. Meanwhile, Sharia is defined as the purpose of Islamic law to protect the five basic human needs (daruriyyat): religion, life, intellect, lineage, and property. In this study, a qualitative-descriptive approach is applied. The content analysis method was used on primary and secondary literature, which includes classical literature, exegesis, and contemporary journals. The research results show that the Maqashid Al-Qur'an provides guidelines for universal values relevant to global issues, while the Maqashid Syariah focuses on the application of practical law. Their goals are the same: to produce maslahah (benefit) and prevent mafsadah (harm). By offering a framework that integrates two paradigms to address modern issues such as social justice, the environment, and global peace, this research contributes to the development of Islamic studies